OCORRÃŠNCIA E DISPERSÃƒO DA POLIEDROSE NUCLEAR DO CURUQUERÃŠ DO ALGODOEIRO ð˜ˆð˜ð˜¢ð˜£ð˜¢ð˜®ð˜¢ ð˜¢ð˜³ð˜¨ð˜ªð˜ð˜ð˜¢ð˜¤ð˜¦ (HÃ¼bner, 1818) (LEP., NOCTUIDAE) - Andrade, C. F. S.; Habib, M. E. M. (REVISTA DE AGRICULTURA, 2020)
OCORRÃŠNCIA E DISPERSÃƒO DA POLIEDROSE NUCLEAR DO CURUQUERÃŠ DO ALGODOEIRO ð˜ˆð˜ð˜¢ð˜£ð˜¢ð˜®ð˜¢ ð˜¢ð˜³ð˜¨ð˜ªð˜ð˜ð˜¢ð˜¤ð˜¦ (HÃ¼bner, 1818) (LEP., NOCTUIDAE)